2020
DOI: 10.1007/s12325-020-01328-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Pirfenidone in Advanced Idiopathic Pulmonary Fibrosis: A Nationwide Post-Marketing Surveillance Study in Korean Patients

Abstract: Aim: The efficacy and safety of pirfenidone have been previously demonstrated in patients with mild-to-moderate idiopathic pulmonary fibrosis (IPF). However, the effect of pirfenidone in patients with advanced IPF remains unclear. Here, we investigated the effects of pirfenidone against advanced IPF in a real-world setting. Methods: A prospective nationwide post-marketing study was conducted on 258 patients from 10 Korean institutions. Patients with a predicted forced vital capacity (FVC) less than 50% or a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
(63 reference statements)
1
24
0
2
Order By: Relevance
“…[4,5] The use of agents to prevent or reduce fibrotic status, such A preliminary version of this report was made publicly available as a socalled preprint at a nonprofit repository (Authorea) with DOI number: https://doi.org/10.22541/au.158802198.88770371 as pirfenidone, may be therapeutically effective in preventing serious or fatal complications. Pirfenidone is the drug of choice in the treatment of idiopathic pulmonary fibrosis (IPF) [6] and with a pleiotropic mechanism of action reduces the fibrotic and inflammatory state of lung tissue. Its therapeutic efficacy could also benefit healed patients with consequences on lung tissue with a state of fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The use of agents to prevent or reduce fibrotic status, such A preliminary version of this report was made publicly available as a socalled preprint at a nonprofit repository (Authorea) with DOI number: https://doi.org/10.22541/au.158802198.88770371 as pirfenidone, may be therapeutically effective in preventing serious or fatal complications. Pirfenidone is the drug of choice in the treatment of idiopathic pulmonary fibrosis (IPF) [6] and with a pleiotropic mechanism of action reduces the fibrotic and inflammatory state of lung tissue. Its therapeutic efficacy could also benefit healed patients with consequences on lung tissue with a state of fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with this degree of physiologic impairment have been excluded from clinical trials of antifibrotic therapies. Therefore there is a dearth of information about the clinical course, functional impairment as well as the safety and efficacy of antifibrotic therapy in this population, although mining of registry data or recent real-world papers have focused on this issue, providing encouraging results in this neglected population [10][11][12][13]21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients who initially present with milder impairment but progress to more advanced disease despite treatment with antifibrotic therapy are often not candidates for enrollment in addon treatment trials. Despite some recent data in this population [10][11][12][13], there remains a large void of information regarding the efficacy of antifibrotic therapy in patients with severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that bilateral interstitial pneumonia caused by COVID-19, so called because it attacks the tissue covering the lung alveoli, is associated with the presence of fibrotic tissue caused by excess collagen (fibrosis) in the lung crevice with associated hyperinflammation present. In this direction, the use of a pharmacological approach to reduce or prevent fibrotic status, with antifibrotic agents such as pirfenidone, used with demonstrated clinical efficacy in idiopathic pulmonary fibrosis [4] can be a valuable aid in the prevention of serious or fatal complications from COVID-19 in patients with ongoing infection, or in those already healed with residual fibrotic lung lesions [5].…”
mentioning
confidence: 99%